An Amplicon Panel for High-Throughput and Low-Cost Genotyping of Yesso Scallop Mizuhopecten yessoensis - Ben J. G. Sutherland; Chen Yin Walker; Denman Moody; Chelsea Bennett; Marissa Wright-LaGreca; Chloe Shamash-McLaughlin; Karen Leask; Daniel Roth; Megan Lebeuf; Timothy J. Green (Marine Biotechnology, 2026)

Differential motor unit firing rate and hypertrophic adaptations of the vastus lateralis despite similar strength increases following high-load versus combined high- and low-load resistance training interventions - Alex A. Olmos; Daniel J. Lawson; Stephanie A. Sontag; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Allen L. Redinger; Sean M. Gamache; Michael A. Trevino (Experimental Brain Research, 2026)

Hydraulic Optimization of Shaft Hydropower Plant Intake Configurations Using 3D-CFD: the At-Bashy Case, Kyrgyzstan - Bertalan Alapfy; Daniel S. Hayes; Moritz Roth; Nils Rüther (Environmental Management, 2026)
The integration of shaft hydropower plant (SHPP) modules into existing weir structures offers a compact and potentially environmentally compatible solution for low-head hydropower generation. However, site-specific geometric constraints and operational variability can substantially affect intake hydraulics and, consequently, ecological performance. This study presents a structured three-dimensional CFD-based hydraulic optimization framework applied to the At-Bashy demonstration site (Kyrgyzstan), representing a SHPP configuration integrated into an existing gated weir. Nine intake configurations were systematically evaluated by varying trash rack length (6–8 m) and submergence above the rack (2.00–2.85 m) while maintaining constant turbine and bypass discharges. Fish-relevant hydraulic indicators were quantified within defined near-rack volumes of interest using time-averaged metrics. In addition to mean velocity components, tail-based indicators of extreme downward-directed velocities and statistical measures of free-surface variability were assessed. Results demonstrate that increasing submergence consistently reduces extreme downward velocities and homogenizes the near-rack flow field. Increasing rack length primarily lowers average downward deflection. Strong upstream flow asymmetry caused by geometric constraints induces localized flow separation and heterogeneous vertical flow velocity cores, highlighting the importance of site-specific hydraulic assessments. A rack length of 7 m combined with operational submergence levels between 2.35 m and 2.85 m provides a balanced compromise between ecological performance and structural-economic feasibility. The study confirms that SHPP intake optimization cannot rely on generalized empirical rules but requires site-adapted numerical evaluation. The presented CFD-based framework provides a transparent and transferable methodology for hydraulic optimization of SHPP intake configurations.

Correction: The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

The influence of high-load and combined high- and low-load resistance training on electromyographic behavior during an absolute muscular endurance task - Alex A. Olmos; Stephanie A. Sontag; Daniel J. Lawson; Lyric D. Richardson; Brenden L. Roth; Sunggun Jeon; Jaiden C. Smith; Allen L. Redinger; Michael A. Trevino (European Journal of Applied Physiology, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Cefepime versus carbapenems for treatment of AmpC beta-lactamase-producing Enterobacterales bloodstream infections - Julia Herrmann; Anne-Valérie Burgener-Gasser; Daniel Goldenberger; Jan Roth; Maja Weisser; Pranita D. Tamma; Sarah Tschudin-Sutter (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Cefepime is recommended for treating infections caused by AmpC beta-lactamase-producing Enterobacterales (AmpC-PE), though supporting evidence is limited. Therefore, this study compared outcomes associated with cefepime versus carbapenem therapy for bloodstream infections (BSIs) caused by AmpC-PE after phenotypic exclusion of ESBL-co-producing isolates. Methods This retrospective cohort study compared definite cefepime versus carbapenem treatment for AmpC-PE BSI in hospitalized patients of the University Hospital Basel, Switzerland, between 01/2015 and 07/2020. Primary outcomes included in-hospital death, renal impairment and neurologic adverse events; secondary outcomes included length of hospital stay and recurrent infection. Results Two hundred and seventy episodes of AmpC-PE BSI were included, 162, 77 and 31 were treated with a carbapenem, cefepime and other antibiotics, respectively. Patients treated with carbapenems were more likely to be transferred to the ICU on admission and more frequently had central venous catheter as a source of infection. In uni- and multivariable analyses, primary and secondary outcomes did not differ between the two treatment groups, except for more frequent occurrence of neurological adverse events among patients treated with carbapenems and shorter length of hospital stay among survivors treated with cefepime. Conclusion After excluding isolates with phenotypic ESBL-co-production, cefepime was not associated with adverse outcomes compared to carbapenems when used to treat BSIs caused by AmpC-PE. Our study provides evidence to support the use of cefepime as a safe treatment strategy for AmpC-PE BSI, particularly in clinically stable patients without initial renal impairment or increased susceptibility to neurological adverse events.

Thermal hazards assessment of three azo nitrile compounds - Cuixian Yang; Dylan Aljović; Thomas P. Vickery; Megan Roth; Daniel J. Muzzio (Process Safety and Environmental Protection, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Drivers of tree-related microhabitat profiles in European and Oriental beech forests - Giorgi Mamadashvili; Antoine Brin; Claus Bässler; Vasyl Chumak; Maksym Chumak; Valeriia Deidus; Lars Drössler; Céline Emberger; Kostadin B. Georgiev; Tigran Ghrejyan; Martin M. Gossner; Ruslan Hleb; et al. (Biological Conservation, 2023)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Extremely rapid, Lagrangian modeling of 2D flooding: A rivulet-based approach - W. Brent Daniel; Corinne Roth; Xue Li; Cindy Rakowski; Tim McPherson; David Judi (Environmental Modelling & Software, 2023)

Why are adaptive facades not widely used in practice? Identifying ecological and economical benefits with life cycle assessment - David Borschewski; Michael P. Voigt; Stefan Albrecht; Daniel Roth; Matthias Kreimeyer; Philip Leistner (Building and Environment, 2023)

In-situ comparison between the energy performance of an in-slab gas heating system and a split system air conditioning in classrooms - Georgios Kokogiannakis; Daniel Daly; Clayton McDowell; James Roth; Michael Tibbs; Paul Cooper (Energy and Buildings, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Particle‐associated and free‐living bacterial communities in an oligotrophic sea are affected by different environmental factors - Dalit Roth Rosenberg; Markus Haber; Joshua Goldford; Maya Lalzar; Dikla Aharonovich; Ashraf Al‐Ashhab; Yoav Lehahn; Daniel Segrè; Laura Steindler; Daniel Sher (Environmental Microbiology, 2021)
Summary In the oceans and seas, environmental conditions change over multiple temporal and spatial scales. Here, we ask what factors affect the bacterial community structure across time, depth and size fraction during six seasonal cruises (2 years) in the ultra‐oligotrophic Eastern Mediterranean Sea. The bacterial community varied most between size fractions (free‐living (FL) vs. particle‐associated), followed by depth and finally season. The FL community was taxonomically richer and more stable than the particle‐associated (PA) one, which was characterized by recurrent ‘blooms’ of heterotrophic bacteria such as Alteromonas and Ralstonia . The heterotrophic FL and PA communities were also correlated with different environmental parameters: the FL population correlated with depth and phytoplankton, whereas PA bacteria were correlated primarily with the time of sampling. A significant part of the variability in community structure could, however, not be explained by the measured parameters. The metabolic potential of the PA community, predicted from 16S rRNA amplicon data using PICRUSt, was enriched in pathways associated with the degradation and utilization of biological macromolecules, as well as plastics, other petroleum products and herbicides. The FL community was enriched in predicted pathways for the metabolism of inositol phosphate, a potential phosphorus source, and of polycyclic aromatic hydrocarbons.

Dynamic macromolecular composition and high exudation rates in Prochlorococcus - Dalit Roth‐Rosenberg; Dikla Aharonovich; Anne Willem Omta; Michael J. Follows; Daniel Sher (Limnology and Oceanography, 2021)
Every living cell is composed of macromolecules such as proteins, DNA, RNA, and pigments. The ratio between these macromolecular pools depends on the allocation of resources within the organism to different physiological requirements, and in turn affects biogeochemical cycles of elements such as carbon, nitrogen, and phosphorus. Here, we present detailed measurements of the macromolecular composition of Prochlorococcus MIT9312, a representative strain of a globally abundant marine primary producer, as it grows and declines due to nitrogen starvation in laboratory batch cultures. As cells reached stationary stage and declined, protein per cell decreased by ~ 30% whereas RNA per cell and pigments per cell decreased by ~ 75%. The decline stage was associated with the appearance of chlorotic cells, which had higher forward scatter (a proxy for cell size) but lower chlorophyll autofluorescence, as well as with changes in photosynthetic pigment composition. Specifically, during culture decline divinyl‐chlorophyll‐like pigments emerged, which were not observed during exponential growth. These divinyl‐chlorophyll‐like pigments were also observed in natural samples from the Eastern Mediterranean. Over 90% of the carbon fixed by Prochlorococcus MIT9312 (but not of a different strain, NATL2A) was released into the growth media under these laboratory conditions. Variations in RNA/protein indicate that, broadly defined, the macromolecular composition of Prochlorococcus MIT9312 is more similar to eukaryotic phytoplankton than to marine heterotrophic bacteria, possibly due to the significant investment in photosynthetic machinery of phototrophs.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Typologies of individuals vulnerable to insomnia: a two-step cluster analysis - Daniel Ruivo Marques; Ana Allen Gomes; Vanda Clemente; Christopher L. Drake; Thomas Roth; Charles M. Morin; Maria Helena Pinto de Azevedo (Sleep and Biological Rhythms, 2021)

Evaluation of Microwave Vacuum Drying as an Alternative to Freeze-Drying of Biologics and Vaccines: the Power of Simple Modeling to Identify a Mechanism for Faster Drying Times Achieved with Microwave - Akhilesh Bhambhani; Justin Stanbro; Daniel Roth; Elizabeth Sullivan; Morrisa Jones; Robert Evans; Jeffrey Blue (AAPS PharmSciTech, 2021)
Vial-based lyophilization for biopharmaceuticals has been an indispensable cornerstone process for over 50 years. However, the process is not without significant challenges. Capital costs to realize a lyophilized drug product facility, for example, are very high. Similarly, heat and mass transfer limitations inherent in lyophilization result in drying cycle on the order of several days while putting practical constraints on available formulation space, such as solute mass percentage or fill volume in a vial. Through collaboration with an external partner, we are exploring microwave vacuum drying (MVD) as a faster drying process to vial lyophilization wherein the heat transfer process occurs by microwave radiation instead of pure conduction from the vial. Drying using this radiative process demonstrates greater than 80% reduction in drying time over traditional freeze-drying times while maintaining product activity and stability. Such reduction in freeze-drying process times from days to several hours is a welcome change as it enables flexible manufacturing by being able to better react to changes either in terms of product volume for on-demand manufacturing scenarios or facilities for production ( e.g ., scale-out over scale-up). Additionally, by utilizing first-principle modeling coupled with experimental verification, a mechanism for faster drying times associated with MVD is proposed in this article. This research, to the best of our knowledge, forms the very first report of utilizing microwave vacuum drying for vaccines while utilizing the power of simplified models to understand drying principles associated with MVD.

Maternal-Child Exposures to Persistent Organic Pollutants in Dhaka, Bangladesh - Michael Leung; Therese Haugdahl Nøst; Frank Wania; Eszter Papp; Dorte Herzke; Abdullah Al Mahmud; Daniel E. Roth (Exposure and Health, 2020)

Changes in the distribution of Michigan crayfishes and the influence of invasive rusty crayfish (Faxonius rusticus) on native crayfish substrate associations - Kelley R. Smith; Brian M. Roth; Michael L. Jones; Daniel B. Hayes; Seth J. Herbst; Nicholas Popoff (Biological Invasions, 2019)

Prochlorococcus in the lab and in silico: The importance of representing exudation - Michal Grossowicz; Dalit Roth‐Rosenberg; Dikla Aharonovich; Jacob Silverman; Michael J. Follows; Daniel Sher (Limnology and Oceanography, 2017)
In this study, we test the applicability of the Droop/Caperon internal stores model to describe the growth and decline of the globally abundant marine cyanobacterium Prochlorococcus in batch culture as a function of internal and external inorganic and organic carbon and nitrogen. A rigorous parameter fitting exercise, constrained by the measured cell density, ammonium and inorganic carbon concentrations, revealed many different combinations of parameter values that provided equally good model‐data fit. Introducing data on C : N ratio from the published literature provided additional constraints which could only be satisfied with a structural change to the model. The simplest addition that satisfied these constraints and improved quantitative overall model‐data agreement was to explicitly represent excretion, which was predicted to account for 0.03–8.5% of the daily primary productivity; somewhat lower than previous estimates based on radiotracer incorporation. We argue that this significant and biologically meaningful process should not be neglected in models of marine phytoplankton.

Carry-over effects and foraging ground dynamics of a major loggerhead breeding aggregation - Simona A. Ceriani; James D. Roth; Anton D. Tucker; Daniel R. Evans; David S. Addison; Christopher R. Sasso; Llewellyn M. Ehrhart; John F. Weishampel (Marine Biology, 2015)

Report on the 43rd Annual Meeting of the DPG-Working Group Nematology - Matthias Daub; Ulrike Hakl; Leendert PG Molendijk; Corrie Schomaker; Thomas H Been; Thea G van Beers; Sevda Jivishova; Emil Jivishov; Michael Keusgen; Roman Bluemel; Daniel Fischer; Florian MW Grundler; et al. (Journal of Plant Diseases and Protection, 2015)

Discrimination between random and non-random processes in early bacterial colonization on biomaterial surfaces: application of point pattern analysis - Daniel Siegismund; Anja Schroeter; Claudia Lüdecke; Andreas Undisz; Klaus D. Jandt; Martin Roth; Markus Rettenmayr; Stefan Schuster; Sebastian Germerodt (Biofouling, 2014)

Are all eggs created equal? A case study from the Hawaiian reef-building coral Montipora capitata - Jacqueline L. Padilla-Gamiño; Robert R. Bidigare; Daniel J. Barshis; Ada Alamaru; Laetitia Hédouin; Xavier Hernández-Pech; Frederique Kandel; Sherril Leon Soon; Melissa S. Roth; Lisa J. Rodrigues; Andrea G. Grottoli; Claudia Portocarrero; et al. (Coral Reefs, 2013)

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Die zentrifugal-mikrofluidische Plattform - Daniel Mark; Günter Roth; Roland Zengerle; Felix von Stetten (BIOspektrum, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

Budesonide effects on Clara cell under normal and allergic inflammatory condition - Felix Daniel Roth; Amado Alfredo Quintar; Elisa M. Uribe Echevarría; Alicia Inés Torres; Agustín Aoki; Cristina Alicia Maldonado (Histochemistry and Cell Biology, 2006)

A comparison of estimated and calculated effective porosity - Daniel B. Stephens; Kuo-Chin Hsu; Mark A. Prieksat; Mark D. Ankeny; Neil Blandford; Tracy L. Roth; James A. Kelsey; Julia R. Whitworth (Hydrogeology Journal, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Light-driven periodic changes in urocanase activity of a heterotrophic bacterium - Daniel H. Hug; Dennis Roth; John K. Hunter (Archives of Microbiology, 1972)